Glutamate Signaling in Healthy and Diseased Bone - Cowan, Robert W.; Seidlitz, Eric P.; Singh, Gurmit (Frontiers in Endocrinology, 2012)
Bone relies on multiple extracellular signalling systems to maintain homeostasis of its normal structure and functions. The amino acid glutamate is a fundamental extracellular messenger molecule in many tissues, and is used in bone for both neural and non-neural signalling. This review focuses on the non-neural interactions, and examines the evolutionarily ancient glutamate signalling system in the context of its application to normal bone functioning and discusses recent findings on the role of glutamate signalling as they pertain to maintaining healthy bone structure. The underlying mechanisms of glutamate signalling and the many roles glutamate plays in modulating bone physiology are featured, including those involved in osteoclast and osteoblast differentiation and mature cell functions. Moreover, the relevance of glutamate signalling systems in diseases that affect bone, such as cancer and rheumatoid arthritis, is discussed, and will highlight how the glutamate system may be exploited as a viable therapeutic target. We will identify novel areas of research where knowledge of glutamate communication mechanisms may aid in our understanding of the complex nature of bone homeostasis. By uncovering the contributions of glutamate in maintaining healthy bone, the reader will discover how this complex molecular signalling system may advance our capacity to treat bone pathologies.